A prospective, randomized, double-blinded control study on comparison of tramadol, clonidine and dexmedetomidine for post spinal anesthesia shivering - Venkatraman,Rajagopalan (2018)
Abstract Introduction Shivering, a common intraoperative problem under spinal anesthesia increases the oxygen consumption considerably and is uncomfortable and distressing to the patient, anesthesiologist as well as surgeon. The present study was designed to explore the effectiveness of tramadol, clonidine and dexmedetomidine in the treatment of post spinal anesthesia shivering and to look for their adverse effects. Methods This prospective, randomized, double blinded control study was done on 90 patients who developed shivering under spinal anesthesia. They were randomly allocated into three groups with Group T receiving tramadol 1 mg.kg-1, Group C getting clonidine 1 mcg.kg-1 and Group D patients receiving dexmedetomidine 0.5 mcg.kg-1. The time taken to control shivering, recurrence rate, hemodynamic variables, sedation score and adverse effects were observed. Results Dexmedetomidine was faster in the control of shivering in 5.7 ± 0.79 minutes (min) whereas tramadol took 6.76 ± 0.93 min and clonidine was slower with 9.43 ± 0.93 min. The recurrence rate was much lower in the dexmedetomidine group with 3.3% than for clonidine (10%) and tramadol (23.3%) group. The sedation achieved with dexmedetomidine was better than clonidine and tramadol. The tramadol group had more cases of vomiting (four) and dexmedetomidine group had six cases of hypotension and two cases of bradycardia. Two of the clonidine patients encountered bradycardia and hypotension. Conclusion Dexmedetomidine is better than tramadol and clonidine in the control of shivering because of its faster onset and less recurrence rate. Though complications are encountered in the dexmedetomidine group, they are treatable.